Multi-Sensorial Architectural Design As A Design Element For The Visually Impaired (A Potential Equity And Universal Design For Diffable) - Apritasari, Yaseri D.; Ravelino, Parlindungan; Wibowo, Felise Livia (MAJ - Malaysia Architectural Journal, 2025)
Visually impaired people have limitations and challenges in understanding the built environment. The current one focuses on exploring the built environment through the visual elements of architecture, whereas their condition is limited to visuals. The purpose of this study is to explore spatial quality to meet the needs of blind people. As well as demonstrating the importance of designs that explore multi-sensory architecture for them. The research methodology is qualitative with content analysis that explores the phenomenon of the experience of visually impaired people. In this research, we will explore the experiences form one of the member of the National Commission of Disabilities Indonesia in perceiving space and the surrounding environment. As well as their personal experience interpreting space through multi-sensory in the form of haptic perception (active-passive), auditory perception, and olfactory perception. They will extract from all multisensory architectures which implementation is most effective for their needs. The results show the importance of multisensory architectural design that supports equity and universal design for visually impaired people. It also empowers them to live independently, safely, and comfortably.